2021
DOI: 10.3390/jcm10143041
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Milieu of Amniotic Fluid Increases with Chorio-Deciduitis Grade in Inflammation-Restricted to Choriodecidua, but Not Amnionitis, of Extra-Placental Membranes

Abstract: No information exists about whether intra-amniotic inflammatory response increases with a chorio-deciduitis grade in the context of both inflammation-restricted to chorio-decidua and amnionitis of extra-placental membranes among spontaneous preterm births. The objective of current study is to examine this issue. A study population included 195 singleton pregnant women with chorio-deciduitis, and who spontaneously delivered at preterm (21.6~35.7 weeks) within 7 days of amniocentesis. We examined intra-amniotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
(158 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, fetal health can also be investigated through placental pathology, where the odds of neonatal intensive care unit (NICU) admission were twice as high in pregnancies with placental pathologies in addition to placental abruption [ 4 ]. Furthermore, inflammation in the extra-placental membranes showed that the inflammatory milieu of amniotic fluid increases with chorio-deciduitis grade, but not amnionitis of these membranes [ 5 ].…”
mentioning
confidence: 99%
“…Interestingly, fetal health can also be investigated through placental pathology, where the odds of neonatal intensive care unit (NICU) admission were twice as high in pregnancies with placental pathologies in addition to placental abruption [ 4 ]. Furthermore, inflammation in the extra-placental membranes showed that the inflammatory milieu of amniotic fluid increases with chorio-deciduitis grade, but not amnionitis of these membranes [ 5 ].…”
mentioning
confidence: 99%